Lisbon Strategy Legacy – “Europe 2020” Outlook: Continuity and Change in UE Economic Policy - Grosse, Tomasz Grzegorz (Journal of Public Governance, 2010)
The aim of this article is to compare the Lisbon and “Europe 2020” EU economic and social strategies. The analysis is focused on “path dependency” of historical trends as well as on new tendencies in management methods and policy priorities. The changes in the new EU Strategy are due to external circumstances and are rather evolutionary. They have a limited impact on the quality of the Strategy’s implementation.